Implementation of an Emergency Community Restriction Policy (PPKM Darurat) for COVID-19 Mitigation in Surabaya - Pribadi, Frita Ayu (KnE Social Sciences, 2022)
Various efforts have been made by the government in Indonesia with the aim of reducing the number of COVID-19 cases, one of which is the implementation of emergency community activity restrictions (PPKM Darurat), which was carried out from July 3 to the extension of July 25, 2021. The purpose of this study was to analyze the implementation of this policy in the city of Surabaya. The theoretical model of Grindle was used, with two successful policy implementations consisting of content of policy and context of implementation. This research used qualitative descriptive methods and secondary data sources such as books, scientific journals, related internet websites, official government reports, and others. The results demonstrated that the content of policy indicators had not been explained in detail regarding the administrative sanctions for those who violated the PPKM Darurat policy. Meanwhile, following the implementation of the PPKM Darurat policy, the number of COVID-19 cases in Surabaya did not decrease. Keywords: policy implementation, PPKM Darurat, COVID-19